2019
DOI: 10.2478/ata-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tablets Made from Mixture of Charred Agricultural Residues with and Without Embedded Fertilizer

Abstract: Densification of biochar can reduce transportation and handling costs, as well as significantly decrease loss of biochar during soil application. Although the nutrient-rich biochar tablets may be a potential cost-effective slow-release fertilizer in soil, there is a lack of information on characterization of mixtures of rubber tree twigs and rice residues tablets with embedded NPK fertilizer. Objective of this work was to determine the physical and chemical properties of biochar tablets with and without embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Dong et al [29] also reported increase in soil C with increasing biochar application. On the contrary, the biochar tablet embedded fertilizer application (T5) demonstrated lower soil total C. This is because the oxidized compounds on the surface of the biochar tablet embedded with fertilizer (T5) which reacted with mineral fertilizer might have shifted the non-labile C compounds to more labile C compounds [30] followed by them being decomposed by the soil microorganisms. The highest soil total N in T4 was due to the higher amount of the biochar in the biochar tablets (38 g).…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al [29] also reported increase in soil C with increasing biochar application. On the contrary, the biochar tablet embedded fertilizer application (T5) demonstrated lower soil total C. This is because the oxidized compounds on the surface of the biochar tablet embedded with fertilizer (T5) which reacted with mineral fertilizer might have shifted the non-labile C compounds to more labile C compounds [30] followed by them being decomposed by the soil microorganisms. The highest soil total N in T4 was due to the higher amount of the biochar in the biochar tablets (38 g).…”
Section: Discussionmentioning
confidence: 99%
“…Pine needles are one of such waste materials that not only ruin the virgin forest through forest inferno, but also affect the fertility of forest land (Dhaundiyal and Gupta, 2014). Another scope of using biological waste (Lee et al, 2019) is to curtail the depletion of fossil fuel reservoirs. It has become difficult to curb emission for some of the fastest growing economies of the world like China and India.…”
mentioning
confidence: 99%
“…Their utilization is closely tied to the requirements for the pellet quality. Multiple scientists investigate the pellet quality in Slovakia, as well as abroad (Dumitrascu et al, 2018;Jiang et al, 2016;Lee et al, 2019;Spirchez et al, 2019;Zamorano et al, 2011), who evaluated the pellet quality on the basis of their composition, density, moisture content, durability, etc. Zafari and Kianmehr (2012) have dealt with the issue of effects of temperature, pressure and moisture on durability of cattle manure pellets.…”
mentioning
confidence: 99%